Dance, Music and Dramaturgy: collaboration plan and dramaturgical apparatus - Lucas, João Paulo; Lignelli (Universidade de Brasilia – UnB, Brasilia/DF, Brazil), César (Revista Brasileira de Estudos da Presença, 2022)
The unfolding of the concept of dramaturgy and the problematics of contemporary choreography are, today, a vast and diverse field of research, bearing numerous disclosures that lead to their reciprocal implication. Apart from that, dance and music share significant complementary ties allowing for the consideration of a common compositional inquiry. Reflecting on the compositional processes of dance and music, this article cross-examines the collaboration between choreographers and composers, integrating the incidence of dramaturgy in the strategies of choreographic and musical composition.